Editorial. Issue 1 (1st March 2022) - Welch, Penny; Wright, Susan
Abstract : This issue of Learning and Teaching: The International Journal of Higher Education in the Social Sciences includes work by authors from Austria, Denmark, the United Kingdom, Taiwan, Brazil and Sweden. The five articles cover a diverse range of topics: the third mission of universities, doctoral supervision, internationalisation of higher education, neoliberal think tanks in higher education, and an innovation in the teaching of political thought.